2006
DOI: 10.1007/s00438-006-0180-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of two uvrA genes of Xanthomonas axonopodis pathovar citri

Abstract: Two uvrA-like genes, designated uvrA1 and uvrA2, that may be involved in nucleotide excision repair in Xanthomonas axonopodis pv. citri (X. a. pv. citri) strain XW47 were characterized. The uvrA1 gene was found to be 2,964 bp in length capable of encoding a protein of 987 amino acids. The uvrA2 gene was determined to be 2,529 bp with a coding potential of 842 amino acids. These two proteins share 71 and 39% identity, respectively, in amino acid sequence with the UvrA protein of Escherichia coli. Analyses of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Deletion of pigC and pigG in X. campestris resulted in enhanced susceptibility to radiation from natural light but not to UV (Poplawsky et al 2000). Several UV sensitive mutants were identified in different Xanthomonas strains; most are related to response to oxidative stress and DNA repair (Martínez et al 1997;Shen et al 2007;Tondo et al 2016).…”
Section: Response To Radiation and Lightmentioning
confidence: 99%
“…Deletion of pigC and pigG in X. campestris resulted in enhanced susceptibility to radiation from natural light but not to UV (Poplawsky et al 2000). Several UV sensitive mutants were identified in different Xanthomonas strains; most are related to response to oxidative stress and DNA repair (Martínez et al 1997;Shen et al 2007;Tondo et al 2016).…”
Section: Response To Radiation and Lightmentioning
confidence: 99%
“…It has been suggested that UvrA2 proteins are rather involved in resistance to DNA intercalating drugs than in DNA repair (Goosen & Moolenaar, 2008). However, despite the lack of a UvrB‐binding domain, there is evidence that UvrA2 proteins can confer tolerance to DNA damage (Tanaka et al ., 2005; Shen et al ., 2007; Tark et al ., 2008). Recent studies by Timmins et al .…”
Section: Involvement Of Dna Repair Synthesis In Mutagenesismentioning
confidence: 99%
“…It has been suggested that UvrA2 proteins are rather involved in resistance to DNA intercalating drugs than in DNA repair . However, despite the lack of a UvrB-binding domain, there is evidence that UvrA2 proteins can confer tolerance to DNA damage (Tanaka et al, 2005;Shen et al, 2007;Tark et al, 2008). Recent studies by Timmins et al (2009) have revealed that UvrA2 from Deinococcus radiodurans interacts with UvrB, although the interaction is weak and transient.…”
Section: Involvement Of Dna Repair Synthesis In Mutagenesismentioning
confidence: 99%
“…Class II UvrAs, also known as UvrA2, are found in many bacteria living in harsh environments and show a high degree of sequence similarity to UvrA1, but are missing the UvrB interaction domain. The precise role of UvrA2 remains unclear, but there is evidence that UvrA2s play a role in DNA repair and tolerance to DNA damaging agents, such as UV or chemical treatment [60], [61], [62]. The crystal structure of the ADP-bound dimeric drUvrA2 was solved to 2.3 Å resolution (Table 1 and Fig.…”
Section: Nucleotide Excision Repairmentioning
confidence: 99%